Level of HIV/AIDS Awareness among Learners with Physical Disabilities in a Special Secondary School in Kisumu County, Kenya - Adumah, Festus Otieno (JOOUST, 2017)
The value of information concerning reproductive health for learners with physical disabilities cannot be overemphasized. Globally there are 34 million people living with moderate to severe disabilities, 80% of whom live in developing countries. For instance, 10% of the Kenyan population has disabilities, while Kisumu County has 4.8%, the highest proportion in Kenya. In addition, Kisumu County records 15.3% prevalence rate of human immune deficiency virus (HIV), double the national rate of 7.4%, and is ranked 3rd in HIV prevalence rate in the region and highest at 1.6% among people with physical disabilities. Statistics indicate that between 2013 and 2015, youths with physical disabilities who were infected with HIV/AIDS increased from 60.65% to 71.6%. These prevalence rates could be as a result of learners with physical disabilities being unaware of HIV/ AIDS and prevention measures, although there is no evidence to support this. There was therefore need to determine level of HIV/ AIDS awareness among learners with physical disabilities in special secondary schools in Kisumu county. This study specifically sought to find out the level of awareness of risky sexual behaviour; the level of awareness of pre-disposing conditions that increases vulnerability to HIV/AIDS, and level of awareness of HIV/ AIDS preventive measures. The study was guided by the Theory of Reasoned Action behavior, and research design used was concurrent triangulation within a mixed methods approach. Target population was composed of 135 Students, 1 School Principal, 12 Teachers, and 1 County Director of Education. Saturated • technique was used to select all the 149 out of 149 targeted respondents .Questionnaires was used to collect data from learners, while interview schedules was used to collect data from the principal, the County Director of Education and teachers. The reliability of the data collection tools was ascertained through split-half method during the pilot study, while validity of the instruments was checked by 6 experts in a session which also involved the researcher. Trustworthiness of the instrument was ensured using multiple sources and triangulation of data. Quantitative data was analyzed using descriptive statistics, while qualitative data was analyzed using thematic analysis. The study found that learners with physical disabilities do not abstain from sex and exchange sex for money and other favours with multiple partners without using any protection measures. These learners are also exposed to sexual abuse from non-disabled persons who they are unable to resist due to stigmatization emanating from their physical status. Moreover, the learners are aware of the HIV/AIDS preventive measures. The study recommended that Abstinence, Being faithful to one partner and Consistent use of Condom (ABC) slogan of HIV/ AIDS campaign be consistently sensitized upon these learners, and a policy guiding sexual relationship between disabled and non-disabled learners to be formulated and imparted to the learners by all stakeholders including parents. Additionally, reproductive health services should be tailor-made to suit learners with physical disabilities, and adequate security be provided to this population within learning facilities. Further studies are recommended on the influence of parental involvement and the contribution of reproductive health services on HIV/AIDS awareness and prevention among learners with physical disabilities in special secondary schools.